Randomized, Double-Blind, Parallel-Group, Placebo-Controlled Trial of Bupropion as Treatment for Methadone-Emergent Sexual Dysfunction in Men - Yee, Anne; Loh, Huai Seng; Ong, Teng Aik; Ng, Chong Guan; Sulaiman, Ahmad Hatim (SAGE Publications, 2018)
Methadone is largely recognized as an effective treatment for opiate-dependent patients; however, it causes reduced brain dopaminergic action resulting in significant sexual dysfunction. Bupropion is a dopamine reuptake inhibitor which can potentially improve erectile function among male patients on methadone (MMT). This is a phase II, randomized, double-blind, parallel-group, placebo-controlled trial, involving 80 MMT male patients (73.4%) with mean age of 42.83 years ±9.68. These MMT male patients were randomly assigned into two groups to receive bupropion and placebo, respectively. The primary efficacy outcome measure was the difference between the two groups in end-point mean improvement scores using the measurement of Clinical Global Impression Scale adapted for Sexual Function (CGI-SF) at baseline (week 0) and at weeks 2, 4, and 6. Malay version of the sexual desire inventory-2 (SDI-2-BM) and Malay version of International Index of Erectile Function 15 (Mal-IIEF-15) domain scores were evaluated as secondary parameters. Improvement of the end-point mean from baseline were seen across the scores of SDI-2-BM (mean difference = 11.77 ± 2.90, 95% confidence interval (CI) [3.89, 19.54], p <.001) and Mal-IIEF-15 (mean difference = 8.37 ± 2.71, 95% CI [15.75, 0.99], p =.02), and the total plasma testosterone level (mean difference = 4.03, 95% CI [0.90, 7.15], p =.01). A categorical improvement of “much/very much improved” (CGI-SF score = 2) was reported by 58.3% (n = 21/36) of bupropion SR-assigned versus 27.7% (n = 10/36) placebo-assigned patient. Bupropion was well tolerated with no serious adverse events reported other than insomnia (17.7%). Six weeks of bupropion SR treatment reported significant improvement in key aspects of sexual function among male opiate-dependent patients on methadone maintenance treatment with emergent sexual dysfunction.